Are Reviewers' Judgements Influenced by Memo Structure and Conclusions Documented in Audit Workpapers?* - Tan, Hun‐Tong; Yip‐Ow, Jackson (Contemporary Accounting Research, 2001)
Abstract This paper investigates how the initial conclusion reached by the preparer of audit workpapers and the manner with which the preparer structures the associated evidence can influence the reviewer's judgement in an audit setting. We conducted an experiment in which auditors reviewed the work of a preparer who had concluded that the account of the client's major customer was either collectible or not collectible. The preparer's memo was structured in a neutral manner or stylized to emphasize (de‐emphasize) evidence consistent (inconsistent) with the preparer's conclusion. Results showed that reviewers placed less reliance on the conclusions reached by the preparer when the preparer's memo was stylized than when the memo was structured in a neutral manner. These results suggest that reviewers are sensitive to stylization attempts by preparers. Implications of the paper are discussed.